Dynamics of Change in Latin American Literature: Contemporary Women Writers - Adelaida López de Martínez (Studies in 20th & 21st Century Literature, 1996)
Over the last twenty-five years Latin American societies have undergone profound changes. Where once the legalized abuses of dictatorships gave new meaning to the word "silence" for both men and women, now large segments of the population fight hard to sustain democratic regimes throughout the Continent. Repressive governments are being replaced, and shattered economies have begun to recover. Encouraged by the ever-increasing strength of international feminism, Latin American women (from Chiapas, Mexico, to Plaza de Mayo in Argentina) have risen to play key roles in this socio-political reformation. The writing of female authors has proliferated in this environment, and the literary canon of our time has been enriched. This article examines first the impact of twenty-five years of feminism in Latin America, and second, the status of contemporary Latin American women writers within a global context.
Keywords: contemporary women writers; women; Latin American women writers; dictatorship; silence; oppression; governmental oppression; feminism; Chiapas; Mexico; Plaza de Mayo; socio-political reformation